Nurses professional values scale-revised: Psychometric properties of the Turkish version - Süheyla Özsoy; Renginar Özturk Donmez (Nursing Practice Today, 2015)
Background  & Aim: Nurses professional values are standards for action and provide a frame- work for evaluating behaviors. This paper is the report of a study designed to assess the psycho- metric  properties  of  the  Turkish  version  of  the  Nurses  Professional  Values  Scale-Revised (NPVS-R). Methods & Materials: This methodological study was carried out a university hospital in Izmir, the third most populous city in Turkey. The sample consisted of 228 nurses, who were recruited from January to August 2008. Data were collected with a socio-demographic form (11 questions) and the Turkish version of the NPVS-R (26 items). Many researchers in various countries have used NPVS-R to identify the professional values of nurses or nursing students. Content validity, construct validity, internal consistency, and reliability were assessed. A P < 0.050 was considered as statistically significant. Results: Responses to the NPVS-R were subjected to exploratory and confirmatory factor analy- sis. Principal  components  analysis  with varimax  rotation  and Kaiser  normalization  resulted  in four-factor solution explaining 52.41% of the common variance, and four factors named profes- sionalism, caring, activism, and trust. Findings supported internal consistency reliability of four factors with alpha coefficients from 0.72 to 0.86 and a total scale alpha coefficient of 0.92. Total- item correlation coefficients ranged from 0.38 to 0.71. Conclusion: The study findings showed that the Turkish version of the NPVS-R has a good struc- tural characteristic and is a valid and reliable instrument that can be used for measuring profes- sional values.